ESTRATÉGIAS DE SUSTENTABILIDADE E OS 17 OBJETIVOS DE DESENVOLVIMENTO SUSTENTÁVEL: ESTUDO DE CASO EM UMA INDÚSTRIA DE FIOS E CABOS - CARDOSO, ANDERSON (2023)
Subject: after the creation of Agenda 2030 and the 17 Sustainable Development Goals (SDG), by United Nation Organization (UNO) in 2015, the organizations have showed more interesting in being sustainable within what is inserted. To understand the actions of a company operating in the automotive market, this study was carried out, using the theoretical foundation of Strategy as a Social Practice, Sustainability, The 17 SDGs and the Global Compact. Problem/Goals: looking for answering the problem of the searching: which are organization of sustainability strategies that are aligned to the 17 Sustainable Development Goals (SDG)? The general objective was identified by the sustainability strategies focusing in 17 SDGs in a organization located in the city of Irati, South-Center of the Parana State, and the specific objectives were to identify sustainability actions that are part of the organization's daily life; verify the alignment of organizational practices with the 17 SDGs; and propose actions that can help the organization align with the 17 SDGs. Methodology: to develop the research, a questionnaire was administered to the organization's employees to identify the sustainability actions they witness and interviews were carried out using a semi-structured script with three managers, who are representatives of the departments linked to the pillars of sustainability, economic, environmental and social. The research is considered as a case study, consisting of the questionnaire (applied in April 2023), interviews (carried out in June and August 2023), direct observation, document analysis and field diary. To analyze the interviews, the content analysis technique was used. Result; it was possible to identify, in the perception of the company's employees the actions it adopts and which can be related to the 17 Sustainable Development Goals, as well as their level of perception. In interviews with managers, it can be seen that the company does not use sustainability and the 17 SDGs hemes in its daily life, however, it was identified that even though it does not use the nomenclature, the institution considers the environmental, social and economic pillars when developing its strategic plans, as well as being able to list numerous actions and structure them around the 17 SDGs. The main actions identified were structured around SDG 3 – Health and Well-Being, SDG 4 – Quality Education, SDG 8 – Decent Work and Economic Growth, and SDG 12 – Responsible Consumption and Production. Conclusion; the objectives were gotten in the study and it is suggested that the company create indicators for actions related to education, carry out training to disseminate the concepts of sustainability and 17 SDGs, in addition to incorporating them into the company's strategic behavior, and If possible, publicize it to encourage other institutions to seek sustainable development.